Virus-specific nanobody-chimeras degrade the human cytomegalovirus US28 protein in CD34+ cells - Poole, Emma; Schmitt, Janika; Graham, Stephen C.; Kelly, Bernard T.; Sinclair, John (Pathogens, 2024)
After primary infection, human cytomegalovirus (HCMV) establishes lifelong persistence, underpinned by latent carriage of the virus with spontaneous reactivation events. In the immune-competent, primary infection or reactivation from latency rarely causes disease. However, HCMV can cause significant disease in immune-compromised individuals such as immune-suppressed transplant patients. Latency, where the viral genome is carried in the absence of the production of infectious virions, can be established in undifferentiated cells of the myeloid lineage. A number of stimuli can cause virus reactivation from latency to occur, beginning with the induction of viral immediate-early (IE) lytic gene expression. The suppression of viral IE gene expression to establish and maintain latent infection is known to result from a balance of viral and cellular factors. One key viral factor involved in this is the G protein-coupled receptor US28. Recently, we have shown that US28 is targeted for degradation by a modified nanobody (PCTD-Vun100bv) based on the novel PACTAC (PCSK9-antibody clearance-targeting chimeras) approach for targeted protein degradation. Furthermore, we have shown that this PCTD-Vun100bv-induced degradation of US28 results in IE gene expression in experimentally latently infected CD14+ monocytes. However, HCMV also establishes latency in CD34+ bone marrow cells, the progenitors of CD14+ cells. Here, we show that PCTD-Vun100bv also causes US28 degradation in these CD34+ primary cells, again resulting in the induction of viral IE gene expression. Additionally, we show that PCTD-Vun100bv can target US28 in naturally latently infected CD14+ monocytes from an HCMV-seropositive donor, allowing these latently infected cells to be killed by HCMV-specific cytotoxic T cells from that same donor. These observations support the view that targeting US28 for degradation during natural latency could be a tractable 'shock-and-kill' strategy to target the latent HCMV reservoir in myeloid cells.
Gesehen am 02.07.2025